The study of the tumor stem cell properties of CD133+CD44+ cells in the human lung adenocarcinoma cell line A549 - Zhang, H. Z.; Lin, X. G.; Hua, P.; Wang, M.; Ao, X.; Xiong, L. H.; Wu, C.; Guo, J. J. (Cellular and Molecular Biology, 2010)
We studied the tumor stem cell properties of the CD133+CD44+ subpopulation in the human lung adenocarcinoma cell line A549. A549 cells were classified into subpopulations based on differential expression patterns for CD133 and CD44. Cells from different subpopulations were cultured and subcutaneously injected into 32 nude mice. Our Results as following, (1) The majority of A549 cells died, whereas only about 4.11% of cells divided and proliferated to form cell clones. (2) The expression of CD133 and CD44 in proliferative cancer cells was statistically significantly different from that in normal A549 cells (p < 0.001). (3) Cell proliferation in group A (CD133+CD44+) was the fastest among all groups. Cell proliferation in A549 cells was slower than in group A but faster than in groups B (CD133-CD44-), C (CD133-CD44+), and D (CD133+CD44-). (4) The tumorigenic capacity in cells from group A was significantly higher than that in cells from groups B (p<0.001), C (p<0.001) and D (p<0.04). In conclusion, CD133+CD44+ cells in the adenocarcinoma cell line A549 have expressive significant cancer stem cell properties with continuous proliferative capacity and differentiation potential.